Community Resilience and Digital Literacy Model during the COVID-19 Outbreak in Indonesia - Rahmaniah, Syarifah Ema; Syarmiati, Syarmiati; Paramita, Rizqi Ratna (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The spread of COVID-19 has become a global health threat after the World Health Organization said the status of the spread of COVID-19 became a pandemic. The problems that ascend in the effort to avoid outbreaks are due to lack of community awareness and accessibility in supporting Social Distancing and Large-Scale Social Restrictions (PSBB) policies. This research aims to describe the strategy in constructing community resilience and digital literacy during the COVID-19 pandemic by using a human security approach. This research also aims to describe the socio-political impact of spreading fake news during the COVID-19 outbreak.  The research uses qualitative research methods with a literary and empirical approach. The result of the research show the social impact is the declining public trust in the government which is indicated by lack of awareness of citizens in supporting government policies and misleading information related to government policies in dealing with COVID-19. The result also discovered that the difference of political awareness among the public was the main cause of the spread of fake news and hate speech during the COVID-19 outbreak. Another finding stated constructing community resilience can be pursued in four ways 1) increasing social networks and the quality of education; 2) legal legitimacy to maintain security; 3) increasing cooperation and coordination between the government, NGOs, and the community (4) reconstruction of community-based education curricula. This partnership model is evidenced by the collaboration between government, communities and CSOs involved in building resilience and disaster planning. Thus, there are 3 important pillars in realizing community resilience: partnership, involvement, and education. Revitalizing the community resilience and digital literacy is an important strategy that the government and community need to pursue as a infodemic mitigation strategy as part of an early warning system in increasing public immunity against infodemic. This infodemic mitigation model can be pursued by introducing fact-checking techniques for health and pandemic information. We recommend the need for soft skills-based curriculum reconstruction to increase digital literacy and community resilience in educational programs in higher education institutions.